Temperature Sensing in the Short-Wave Infrared Spectral Region Using Core-Shell NaGdF4:Yb3+, Ho3+, Er3+@NaYF4 Nanothermometers - Daria Pominova; Vera Proydakova; Igor Romanishkin; Anastasia Ryabova; Sergei Kuznetsov; Oleg Uvarov; Pavel Fedorov; Victor Loschenov (Nanomaterials, 2020)
The short-wave infrared region (SWIR) is promising for deep-tissue visualization and temperature sensing due to higher penetration depth and reduced scattering of radiation. However, the strong quenching of luminescence in biological media and low thermal sensitivity of nanothermometers in this region are major drawbacks that limit their practical application. Nanoparticles doped with rare-earth ions are widely used as thermal sensors operating in the SWIR region through the luminescence intensity ratio (LIR) approach. In this study, the effect of the shell on the sensitivity of temperature determination using NaGdF4 nanoparticles doped with rare-earth ions (REI) Yb3+, Ho3+, and Er3+ coated with an inert NaYF4 shell was investigated. We found that coating the nanoparticles with a shell significantly increases the intensity of luminescence in the SWIR range, prevents water from quenching luminescence, and decreases the temperature of laser-induced heating. Thermometry in the SWIR spectral region was demonstrated using synthesized nanoparticles in dry powder and in water. The core-shell nanoparticles obtained had intense luminescence and made it possible to determine temperatures in the range of 20–40 °C. The relative thermal sensitivity of core-shell NPs was 0.68% °C−1 in water and 4.2% °C−1 in dry powder.